Effects of unsteady conditions on propulsion generated by the hand`s motion in swimming: a systematic review - Gomes, L. E.; Loss, J. F. (Journal of Sports Sciences, 2015)
The understanding of swimming propulsion is a key factor in the improvement of performance in this sport. Propulsive forces have been quantified under steady conditions since the 1970s, but actual swimming involves unsteady conditions. Thus, the purpose of the present article was to review the effects of unsteady conditions on swimming propulsion based on studies that have compared steady and unsteady conditions while exploring their methods, their limitations and their results, as well as encouraging new studies based on the findings of this systematic review. A multiple database search was performed, and only those studies that met all eligibility criteria were included. Six studies that compared steady and unsteady conditions using physical experiments or numerical simulations were selected. The selected studies verified the effects of one or more factors that characterise a condition as unsteady on the propulsive forces. Consequently, much research is necessary to understand the effect of each individual variable that characterises a condition as unsteady on swimming propulsion, as well as the effects of these variables as a whole on swimming propulsion.